Overcoming Key Barriers for Secondary Cloud Forest Management in Mexico - Toledo-Aceves, T.; Guariguata, Manuel R.; Günter, S.; Porter-Bolland, L.; Merino, L. (MDPI, 2021)
Secondary cloud forests (SCFs), those that regenerate naturally following abandonment of human activities in previously deforested land, are of great value as refuges of high species diversity and for their critical role in hydrological regulation. This opinion paper analyzes the main environmental, socio-economic, and regulatory aspects that currently hamper the sustainable use and conservation of SCFs in Mexico for the provision of timber and ecosystem services. The main constraints identified include contradictory norms and policies and the marginalization of smallholders in timber production activities. Developing economic incentives for forest product harvesting and provision of ecosystem services derived from SCFs, while also addressing legal and normative aspects related to their sustainable use, is paramount. Given the high heterogeneity in floristic composition and stand structure of SCFs among localities, technical and social norms for sustainable use should be sufficiently flexible to allow adaptive management approaches. Future research areas should be focused on monitoring the response of SCFs to silvicultural interventions, documenting existing traditional practices as well as conducting socio-economic analyses of timber production and associated ecosystem services. This is essential for developing sound policies and approaches for the sustainable use and long-term management of SCFs in Mexico.